Изучение адгезионно-когезионной прочности УЗ/МДО кальций-фосфатных покрытий на титане методом скретч тестирования - Казанцева, Екатерина Александровна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
The study of the adhesion-cohesion strength of ultrasound-assisted micro-arc oxidation (US/MAO) calcium phosphate (CaP) coatings on titanium by scratch test method was performed. The US employing during the MAO process, mainly sinewave US action, compared to pulsed US, led to significant increase in the final critical load of LC3 from 18.6 to 30.6 N, at which the coatings completely detached from the substrates, as well as a decrease in the amplitude of acoustic emission signals during scratching.